Effects of Maternal Deprivation on the Prefrontal Cortex of Male Rats: Cellular, Neurochemical, and Behavioral Outcomes - Joko Poleksic (Frontiers Media S.A., 2021)
Stressful events experienced during early life are associated with increased vulnerability of developing psychopathology in adulthood. In the present study, we exposed 9-day-old Wistar rats to 24 h maternal deprivation (MD) with the aim to investigate the impact of early life stress (ELS) on morphological, biochemical, and functional aspects of the prefrontal cortex (PFC), a brain region particularly sensitive to stress. We found that in the superficial medial orbital cortex (MO), young adult male rats had reduced density of GAD67 and CCK immunopositive cells, while the rostral part of the ventral lateral orbital cortex (roVLO) showed a decrease in the density of GAD67 immunopositive cells in both superficial and deep layers. In addition, the superficial rostral part of area 1 of the cingulate cortex (roCg1) and deep prelimbic cortex (PrL) was also affected by MD indicated by the reduction in PV immunopositive cellular density. Furthermore, MD induced upregulation of brain-derived neurotrophic factor (BDNF), while it did not affect the overall expression of Iba1 in neonatal or young adult PFC as measured by Western blot, however, microglial activation in young adult MD rats was detected immunohistochemically in deep layers of MO and infralimbic cortex (IL). Interestingly, when young adult male rats were subjected to a behavioral flexibility test in a T-maze, MD rats showed a subtle impairment in T-maze reversal learning indicating a mildly affected PFC function. Taken together, our findings demonstrated that MD reduced the density of interneurons and induced microglial activation, in particular, PFC areas at young adulthood, and could alter synaptic plasticity accompanied by PFC dysfunction.